Enemies of the people? : how judges shape society - Rozenberg, Joshua (Bristol University Press, 2020)
Do judges use the power of the state for the good of the nation? Or do they create new laws in line with their personal views? When newspapers reported a court ruling on Brexit, senior judges were shocked to see themselves condemned as enemies of the people. But, faced with problems ranging from religious discrimination to end-of-life decisions, the judges cannot avoid hard choices. In this fascinating book, Britain's best-known commentator on the law Joshua Rozenberg, asks how the judges can maintain public confidence while balancing conflicting interests. Do judges use the power of the state for the good of the nation? Or do they create new laws in line with their personal views? When newspapers reported a court ruling on Brexit, senior judges were shocked to see themselves condemned as enemies of the people. But, faced with problems ranging from religious discrimination to end-of-life decisions, the judges cannot avoid hard choices. In this fascinating book, Britain's best-known commentator on the law Joshua Rozenberg, asks how the judges can maintain public confidence while balancing conflicting interests.--